CULTURAL APPROPRIATION DI KALANGAN REMAJA ANALISIS SOSIAL TERHADAP ETIKA BUDAYA DI ERA GLOBALISASI - Muhammad Mona Adha; Risma Margaretha Sinaga; Pujiati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The misuse of cultural elements by adolescents on social media has raised ethical concerns in multicultural societies. Many young people adopt traditional symbols or attire without understanding their original meanings, leading to cultural distortion and disrespect. This study aims to analyze the forms, causes, and ethical awareness of adolescents regarding cultural appropriation in the globalization era. Using a qualitative descriptive approach, data were collected through netnographic observation, in-depth interviews, and visual documentation with adolescents aged 15–19 in Bandar Lampung. The results show that most adolescents engage in cultural appropriation unconsciously, motivated by global trends, peer influence, and low cultural literacy. Common practices include wearing traditional clothes as fashion, remixing traditional dances, and using sacred symbols for entertainment. The findings emphasize the need for cultural ethics education and digital literacy programs to help adolescents appreciate cultural diversity responsibly. This study contributes to the development of multicultural education and ethical digital culture among youth.